Estratégia de maximização do sequestro de carbono na savana brasileira - Oliveira, Henrique Faria de (2019)
The objective of this study was to develop a pragmatic methodology to be replicated on a large scale, providing the indication of species for planting through the natural aptitude of the same to the environmental conditions of each site, as well as estimating its capacity for development and storage of carbon for environmental passive areas identified by the Cadastro Ambiental Rural in the Cerrado domain in the state of Minas Gerais, Brazil. The Logistic Regression method was used, through the Ridge Regression adjustment for species allocation, aiming to minimize the collinearity effect present in the environmental variables and to obtain a logical biological adjustment corresponding to the phytogeographic reality of the same. Four species were evaluated, with data obtained from the Forest Inventory of Minas Gerais, chosen to curb any bias of estimation, assuming that they are abundant, well represented spatially and cover a wide range of diameters, being the species tested the Astronium fraxinifolium Schott ex Spreng, Machaerium opacum Vogel, Qualea grandiflora Mart. and Qualea parviflora Mart. All the models presented good quality in the fit and logical biological correspondence with the environmental factors and the natural distribution of the species. It was possible to define the species allocation in order to optimize carbon sequestration, and consequently the initial development of plantations. Such methodology brings gains in terms of costs, since monospecific plantations with species of rapid local development bring gains in the success of the enterprises, reducing the need for replanting and accelerating the canopy closure, eliminating the competition with invasive weeds early. Vegetational domains of high biological complexity lack metrics for species allocation, because due to the great genotype complexity, inadequate allocation to specific sites has a high probability. It is possible to contribute to the process of monetization of environmental conservation, since from accurate estimates of the storage capacity and present carbon stock, it is possible to create programs and trading methods for carbon credits in the capital market, besides giving precision to the calculation of the fair value to be received for environmental services. All these processes are essential for us to achieve our objectives in the face of the fight against climate change and the dramatic effects that humanity suffers and will suffer with its intensification.